Optimized structure of completely weathered granite roadbed

CN122880047APending Publication Date: 2026-10-09YUNNAN HAIHUILIAN EXPRESSWAY CONSTRUCTION INVESTMENT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611091676.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-09

AI Technical Summary

Benefits of technology

本发明通过构建“包边防渗—隔离控水—格室稳基”三位一体韧性结构,其中包边防渗层形成连续性水力屏障;底部隔离层实现水分纵向迁移的有效阻断;土工格室嵌入改良填料中形成三维约束骨架,协同提升整体抗剪强度与变形协调能力;包边层与底部隔离层通过厚度梯度配置与材料性能互补实现协同防水,包边层作为第一道防线承担地表径流拦截与坡面汇水导排功能,隔离层作为第二道防线阻断毛细上升与深层渗流,二者在竖向形成“上堵—中隔—下截”的三重屏障;该三位一体韧性结构突破传统单一改良路径局限,从水力阻隔、应力分散与结构约束三个维度同步响应全风化花岗岩路基服役需求,有效弥合材料改良性能与工程结构功能之间的转化断层。其核心价值在于将劣化抑制前移至结构层面,通过物理隔离与力学约束双重机制降低水分侵入深度及循环扰动强度,显著延缓矿物溶蚀与孔隙扩张进程,为长期服役性能提供结构性保障。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122880047A_ABST
    Figure CN122880047A_ABST
Patent Text Reader

Abstract

The application discloses a kind of full weathered granite roadbed optimization structure, it is related to road roadbed construction technology field, including bottom isolation layer, edge seepage prevention layer, improved filling layer;Edge seepage prevention layer includes geocell, edge layer;The present application constructs "edge seepage prevention-water control-isolation" trinity toughness structure, wherein edge seepage prevention layer forms continuous hydraulic barrier;Bottom isolation layer realizes the effective blocking of moisture longitudinal migration;Geocell is embedded in improved filler and forms three-dimensional constraint skeleton, and the overall shear strength and deformation coordination ability are synergistically improved;Edge layer and bottom isolation layer are configured by thickness gradient and complementary material performance to realize synergistic waterproofing, edge layer as the first line of defense undertakes surface runoff interception and slope surface catchment drainage function, isolation layer as the second line of defense blocks capillary rise and deep seepage, and the three barriers of "upper block-mid separation-lower cut-off" are formed in vertical direction, and structural guarantee is provided for long-term service performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of roadbed construction technology, specifically to an optimized structure for a fully weathered granite roadbed. Background Technology

[0002] The parent rock of this completely weathered granite is an intrusive granite body from the Yanshanian period. Through long-term hot and humid weathering, it has formed a clay mineral assemblage dominated by kaolinite and illite. Its natural moisture content fluctuates significantly, exhibiting typical characteristics of high plasticity, low permeability, and strong disintegration. In its natural state, this type of rock mass is plastic to soft plastic, with a volume shrinkage rate of 12.3%–18.9% under wet-dry cycles. After immersion in water, its unconfined compressive strength decreases by more than 65%, and its maximum dry density under standard compaction is only 1.48–1.56 g / cm³, while its optimum moisture content is as high as 24.7%–29.5%. The compaction energy requirement is more than 35% higher than that of conventional roadbed fill. During on-site excavation, obvious aggregate dispersion is observed; it rapidly turns into mud upon contact with water, making it difficult to maintain structural bearing capacity and highly susceptible to landslides and collapses. Disasters such as landslides and collapses make it impossible to directly meet the technical specifications for high-grade roadbed filling. For example, the second section of the Menglian-Menghai Expressway in Yunnan (K37+550~K101+965.737) is mostly a shallow-to-medium-sized, dissected ridge-shaped low-mountain landform. The overlying layer is the Quaternary colluvial (Qdl+el) layer, and the lithology is mainly silty clay. In some sections, the overlying layer of completely weathered granite is thick. The engineering properties of this type of soil are generally weak, characterized by low strength, high compressibility, and insufficient water stability. After being used as a roadbed, it is prone to settlement deformation, strength reduction due to wet-dry cycles, seepage deformation, and erosion. It is difficult to meet the requirements of expressway roadbed filling for material strength and durability. It is necessary to solve this problem through material selection, improvement and utilization, or purchasing high-quality fillers.

[0003] Due to the interaction between the pores and water in completely weathered granite, the optimum moisture content is difficult to limit, resulting in poor compaction of the roadbed. Furthermore, the cementation between particles in completely weathered granite is easily affected by the external environment, leading to severe loss of fine particles under rainwater after compaction, which can clog drainage systems. The completely weathered granite after fine particle loss contains a large amount of white quartz and a small amount of black mica-like granular material, which may cause expansion problems. Finally, the compacted completely weathered granite roadbed is prone to loosening under sunlight and rainwater. While traditional cement stabilization methods can improve strength in the short term, their high heat of hydration and large early shrinkage make them prone to inducing network microcracks in high rainfall environments, exacerbating the positive feedback loop of moisture intrusion and structural deterioration. Lime stabilization suffers from slow reaction rates and rapid decay of effective calcium content, with strength growth plateauing after 28 days, making it difficult to support long-term service performance requirements. Hardener-based stabilization materials mostly rely on high-alkali activation systems, which have poor compatibility with residual feldspar, mica, and other silica-alumina components in completely weathered granite, resulting in insufficient cementitious product generation and weak interfacial bonding, leading to generally low strength retention rates after wet-dry cycles. Physical sieving and gradation adjustment are limited by the excessively high natural fine particle content in the completely weathered layer, with less than 30% of the total skeleton material remaining after removing clay particles, making it economically infeasible. The method of adding coarse aggregates results in fluctuating compaction coefficients due to long transportation distances, unstable aggregate specifications, and difficulty in controlling on-site mixing uniformity, failing to meet the technical requirement of ≤5% dry density variation coefficient for layered compaction of high-grade roadbeds. Summary of the Invention

[0004] The main objective of this invention is to provide an optimized structure for fully weathered granite roadbeds, which addresses the problems of instability, softening, deterioration, and drainage difficulties in fully weathered granite roadbeds.

[0005] To achieve the above objectives, the present invention provides an optimized structure for a completely weathered granite roadbed, comprising a bottom isolation layer, multiple sets of edge-sealing seepage-proof layers stacked sequentially on both sides above the bottom isolation layer, and an improved filling layer filled above the bottom isolation layer and connected to the edge-sealing seepage-proof layers. The bottom isolation layer and the edge seepage prevention layer are provided with a crushed stone transition cushion layer; the edge seepage prevention layer includes geocells and an edge layer filled in the geocells. A sloping transition zone is provided between the bottom surface of the edge layer and the top surface of the bottom isolation layer. A transverse drainage slope is provided at the top of the edge layer and it is connected to a longitudinal intercepting ditch; the improved filling layer is partially connected to the geocells and partially located above the geocells.

[0006] As a further improvement of the present invention, the edging layer is constructed with natural clay material to form a lateral sealing layer with a thickness of 0.3–0.6 m, the plasticity index is controlled between 12 and 18, the liquid limit is not higher than 45%, preferably 35%–42%, the natural moisture content fluctuates between 18.5% and 22.3%, and the compaction degree is controlled between 90% and 95%.

[0007] As a further improvement of the present invention, a longitudinal intercepting ditch is provided on the top of the edging layer. The longitudinal intercepting ditch has a cross-sectional size of 30cm×30cm and is lined with HDPE membrane. The water collected on the slope is led to the drainage system on the outside of the roadbed.

[0008] As a further improvement of the present invention, the bottom isolation layer is composed of a composite structure of 60% natural clay and 40% bagasse ash-based low-carbon cementitious components, forming a drainage isolation layer with a thickness of 0.5–1.0m. The bagasse ash content is strictly controlled at 8%–12%, the maximum particle size of the bottom isolation layer does not exceed 37.5 mm, and the compaction degree is controlled at 92%–96%.

[0009] As a further improvement of the present invention, the bottom isolation layer is made of graded continuous crushed stone with 0.3% bagasse ash as a micro-modification.

[0010] As a further improvement of the present invention, the bottom isolation layer is covered with 400g / m² short fiber needle-punched geotextile at both the upper and lower interfaces to enhance the interface friction and filter the migration of fine particles.

[0011] As a further improvement of the present invention, the geocells are made of high-strength polypropylene, with a height of 50–100 mm and a welding distance of 200–400 mm, and are fully laid 0.8 m below the top surface of the modified fill layer; the lower geocells are wrapped around the upper layer, with an overlap length of not less than 1.0 m, and each geocell is fixed at both ends and in the middle with U-shaped nails; before filling the geocell cavity with the modified filler material of completely weathered granite, a 0.5 L / m² emulsified asphalt sealing layer is pre-sprayed to form a temporary waterproof membrane.

[0012] As a further improvement of the present invention, the improved filling layer is a composite combination of completely weathered granite and tailings slag, and the tailings slag is iron tailings sand, with the iron tailings sand blending ratio between 20% and 30%.

[0013] As a further improvement of the present invention, the improved filling layer is a compound combination of fully weathered granite, bagasse ash, tailings slag, and waste incineration bottom ash, with bagasse ash at 15%-25%, tailings slag at 5%-15%, and waste incineration bottom ash at 2%-6%.

[0014] As a further improvement of the present invention, it also includes an alkaline activation system, which adopts a composite activation of NaOH and Na2SiO3, wherein the concentration of NaOH is controlled at 6% to 8%; the modulus of Na2SiO3 is set to 1.2 to 1.4, taking into account both the degree of polymerization of silicon-oxygen tetrahedra and the controllability of the reaction; and 0.3% of a polycarboxylic acid superplasticizer is introduced.

[0015] The beneficial effects of this invention are reflected in: This invention constructs a three-in-one resilient structure consisting of "edge seepage prevention, water isolation and control, and geocell foundation stabilization." The edge seepage prevention layer forms a continuous hydraulic barrier; the bottom isolation layer effectively blocks the vertical migration of water; geocells embedded in the modified fill material form a three-dimensional constrained skeleton, synergistically improving the overall shear strength and deformation coordination; the edge layer and the bottom isolation layer achieve synergistic waterproofing through thickness gradient configuration and complementary material properties. The edge layer, as the first line of defense, undertakes the functions of intercepting surface runoff and draining slope water, while the isolation layer, as the second line of defense, blocks capillary ascent and deep seepage. The two form a triple barrier vertically: "upper blocking, middle isolation, and lower interception." This three-in-one resilient structure breaks through the limitations of traditional single modification paths, simultaneously responding to the service requirements of fully weathered granite subgrades from three dimensions: hydraulic barrier, stress dispersion, and structural constraint, effectively bridging the conversion gap between material modification performance and engineering structural function. Its core value lies in moving the degradation inhibition forward to the structural level. Through the dual mechanisms of physical isolation and mechanical constraints, it reduces the depth of water intrusion and the intensity of cyclic disturbance, significantly delaying the process of mineral dissolution and pore expansion, and providing structural protection for long-term service performance. Attached Figure Description

[0016] Figure 1 This is a schematic diagram of the overall structure of an optimized structure for a completely weathered granite roadbed according to the present invention; Figure 2 This is a detailed drawing of the edge-sealing seepage-proof layer of an optimized structure for a fully weathered granite roadbed according to the present invention. Explanation of reference numerals in the attached figures: 1. Bottom isolation layer; 2. Edge sealing and seepage prevention layer; 201. Geocell; 202. Edge sealing layer; 3. Improved filling layer; 4. Crushed stone transition cushion layer; 5. Geotextile. Detailed Implementation To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the described embodiments are merely some, not all, of the embodiments of this invention. Unless otherwise specified, the embodiments and features described in this application can be combined with each other. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0017] In one embodiment, see Figure 1 , 2 The present invention provides an optimized structure for a fully weathered granite roadbed, comprising a bottom isolation layer 1, multiple sets of edge-sealing seepage-proof layers 2 located on both sides above the bottom isolation layer 1 and stacked sequentially, and an improved filling layer 3 filled above the bottom isolation layer 1 and connected to the edge-sealing seepage-proof layers 2.

[0018] Among them, a crushed stone transition cushion layer 4 is provided between the bottom isolation layer 1 and the edge seepage prevention layer 2; the edge seepage prevention layer 2 includes a geocell 201 and an edge layer 202 filled in the geocell 201. A sloping transition zone is provided between the bottom surface of the edge layer 202 and the top surface of the bottom isolation layer 1. A transverse drainage slope is provided at the top of the edge layer 202 and it is connected to the longitudinal intercepting ditch; the improved filling layer 3 is partially connected to the geocell 201 and partially located above the geocell 201.

[0019] In this embodiment, see Figure 1 The second lateral sealing layer, constructed from natural clay, is 0.3–0.6 m thick. Its plasticity index is controlled between 12 and 18, and its liquid limit is no higher than 45%, preferably 35%–42%. The natural moisture content fluctuates between 18.5% and 22.3%, meeting the moisture content adaptability requirements during construction in high-rainfall areas. The compaction degree is controlled between 90% and 95%. Compaction tests have verified that this type of clay has a maximum dry density of 1.72 g / cm³, an optimal moisture content of 20.6%, and a stable permeability coefficient below 1.0 × 10⁻⁶ after compaction. -7 The material exhibits a permeability of cm / s, strong compatibility with the modified filler interface, and no significant risk of abrupt seepage changes. The fine particle content (less than 0.075mm) is no less than 55%, providing good plasticity and self-healing ability, effectively inhibiting rainwater lateral infiltration along the interface. The second edging impermeable layer utilizes a pre-mixed clay + short-time paving process, with daily operation length controlled within 80 meters, balancing impermeability integrity with the rainy season construction window. The edging clay layer, through plasticity index control and lightweight compaction, maintains a permeability coefficient consistently below 1.0×10⁻⁶. -7 cm / s, forming the first transverse hydraulic barrier.

[0020] The second layer of the edging anti-seepage layer is compacted in layers using a 22-ton vibratory roller. The loose thickness of each layer is controlled at 25±2cm. The number of compaction passes is dynamically adjusted according to the moisture content: when the moisture content is ±1.0% of the optimum moisture content, 1 pass of static compaction + 2 passes of weak vibration + 3 passes of strong vibration are performed; when the moisture content is 1.0% to 2.0% higher than the optimum value, 1 more pass of static compaction is added and the drying time is extended by no less than 6 hours; when the moisture content is 1.0% to 2.0% lower than the optimum value, a mist of water is sprayed and allowed to stand for 2 hours for infiltration before compaction. The overlap width of the compaction tracks is no less than 20cm, and the edge areas are reinforced with a small tamper to ensure no blind spots are left uncompacted. By reducing the lateral seepage rate, the softening of the edges caused by lateral water intrusion is suppressed, ensuring the overall stability of the fill body and preventing structural slippage during continuous heavy rainfall.

[0021] A longitudinal intercepting ditch is set on the top of the edging layer 202. The longitudinal intercepting ditch has a cross-sectional size of 30cm×30cm and is lined with HDPE membrane. The water collected on the slope is led to the drainage system on the outside of the roadbed.

[0022] In this embodiment, the bottom isolation layer 1 is constructed using a composite structure of 60% natural clay and 40% bagasse ash-based low-carbon cementitious components, forming a drainage isolation layer with a thickness of 0.5–1.0 m. The bagasse ash content is strictly controlled at 8%–12%, the maximum particle size of the bottom isolation layer 1 does not exceed 37.5 mm, and the thickness of the bottom isolation layer 1 is based on a 0.7 m benchmark value. Under the premise of ensuring a minimum compaction degree of 92%, the amount of filler used is reduced by 12% compared with the conventional 1.0 m scheme, and carbon emissions are reduced by approximately 8.5 tons / km. The compaction degree of the bottom isolation layer 1 is controlled at 92%–96%, which effectively blocks the dual paths of capillary water rising from the underlying layer and surface runoff infiltration, reducing the fluctuation range of moisture content in the subgrade working area to within ±1.5%.

[0023] In one embodiment, the bottom isolation layer 1 is made of graded continuous crushed stone with 0.3% bagasse ash as a micro-modifier to enhance the interparticle bonding effect, maintain structural integrity under saturation, and suppress capillary water rise to a height not exceeding 0.4 meters.

[0024] The thickness of the bottom isolation layer 1 is determined comprehensively based on three factors: fill height, groundwater level depth, and regional rainfall intensity. For sections with a fill height greater than 12 meters and a groundwater level depth less than 3 meters, a 1.0-meter-thick bottom isolation layer 1 is used; for sections with a fill height between 6 and 12 meters and a groundwater level depth between 3 and 4 meters, a 0.75-meter-thick bottom isolation layer 1 is used; and for sections with a fill height less than 6 meters and a groundwater level depth greater than 4 meters, a 0.5-meter-thick bottom isolation layer 1 is used. All thickness values ​​are reserved with a 10% safety margin to ensure that the minimum functional thickness requirement is still met under the conditions of construction errors and settlement deformation.

[0025] The compaction degree of the bottom isolation layer 1 is controlled within the range of 92% to 96%. The corresponding compaction degree testing adopts a dual control method, mainly using the water injection method and supplemented by a nuclear density meter. The test points are arranged according to the principle of "no less than 2 points per 500m² and no less than 5 points per compacted layer". The compaction process follows a three-stage process of "initial compaction - secondary compaction - final compaction". The initial compaction uses a 26-ton pneumatic tire roller to statically compact twice to seal the surface pores. The secondary compaction uses a 25-ton vibratory roller with medium frequency amplitude rolling four times. The final compaction uses a 30-ton rubber-tired roller to knead and smooth the surface twice. The moisture content control accuracy reaches ±1.5%. The moisture content must be quickly measured and dynamically adjusted before each layer is laid. The surface flatness deviation after compaction does not exceed 8mm / 3m. An overlap width of no less than 30cm is set at the joints and special compaction is carried out.

[0026] The bottom isolation layer 1 is laid with 400g / m² short fiber needle-punched geotextile 5 at both the upper and lower interfaces to enhance the interface friction and filter the migration of fine particles. In this embodiment, see Figure 1Geocell 201 is made of high-strength polypropylene geocell 201, with a height set at 50–100 mm and a welding distance of 200–400 mm. It is fully laid 0.8 m below the top surface of the improved fill layer 3. Through three-dimensional constraint, it suppresses the development of uneven settlement, reduces the plastic cumulative strain under dynamic load by more than 42%, and significantly improves the service adaptability under cyclic load.

[0027] The moisture content of the weathered granite filler in geocell 201 is maintained within the range of optimum moisture content ±1.5%. The welding spacing of geocell 201 is arranged at 300 mm, which not only ensures the vertical constraint stiffness, but also avoids the rolling blind zone caused by excessive welding spacing, so that the coefficient of variation of dry density of layered compaction is stably controlled within 4.2%. The geocell 201 cavity is filled with weathered granite modified material with pore control, which has a strength retention rate of 86.3% and a softening coefficient of 0.78 after dry and wet cycles, effectively blocking the concentrated seepage path of water along the weak surface of the structure.

[0028] The lower geocell 201 is wrapped around the upper geocell 201, with an overlap length of not less than 1.0m. The two ends and the middle of each geocell 201 are fixed with U-shaped nails.

[0029] The distance from the geocell 201 to the edge layer 202 is 2 meters.

[0030] Before filling the 201 geocell with modified weathered granite filler, a 0.5 L / m² emulsified asphalt sealant is sprayed to form a temporary waterproof membrane to prevent initial rainwater infiltration.

[0031] In the section with a fill height of 18.33 meters, geocell 201 uses 100mm high geocells with a lateral restraint stiffness of 42kN / m, which can effectively suppress deep creep deformation. In the 12.33-meter fill section, 80mm high cells were selected to balance constraint effectiveness and ease of construction. After on-site deployment, the filling density increased by 12.6%. In the 10-meter fill height section, 70mm high cell blocks are selected to match the combined thickness of the 202 edge layer and the isolation layer, so as to avoid the top of the cell block being exposed. For sections with a fill height of 6.8 meters or less, 50mm high cells are uniformly selected to ensure that they match the particle size distribution of the improved filler and reduce porosity fluctuations.

[0032] Specifically, see Figure 1 The three-in-one structure of edge seepage prevention layer 2, bottom isolation layer 1, and geocell 201 is designed with a rigid-flexible synergy. A transition crushed stone cushion layer is set at the junction of edge seepage prevention layer 2 and bottom isolation layer 1. A 20mm fitting gap is reserved between the bottom of geocell 201 and the top of bottom isolation layer 1 to ensure that the deformation of each subsystem is coordinated, stress transmission is continuous, and functions support each other under the multi-field coupling of temperature, humidity and load.

[0033] In this embodiment, the improved fill layer 3 is a composite combination of completely weathered granite and tailings slag. The tailings slag is made of iron tailings sand, and the blending ratio of iron tailings sand is between 20% and 30%, preferably 25%.

[0034] In one embodiment, the improved fill layer 3 is a composite mixture of completely weathered granite, bagasse ash, tailings slag, and waste incineration bottom ash. The bagasse ash comprises 15%-25%, preferably 20%; tailings slag comprises 5%-15%, preferably 10%; and waste incineration bottom ash comprises 2%-6%, preferably 4%. Under this ratio, the 7-day compressive strength reaches 5.8 MPa, the 28-day strength reaches 3.6 MPa, and the permeability coefficient is 8.3 × 10⁻⁶. -8 The strength retention rate after wet-dry cycles is 87.2%, fully covering all technical requirements. Response surface methodology verification shows that this combination is at the Pareto optimal frontier of the three-dimensional response surface of strength-permeability-durability, improving the early strength development rate by 23% and reducing the 28-day shrinkage rate by 16% compared to a single solid waste admixture scheme. Furthermore, it maintains a compaction compliance rate of over 99.3% even with a construction control deviation of ±2.0% in moisture content. Bagasse ash is preferentially selected as the main cementing component, with a SiO2+Al2O3 content of 72.6% and a glass content >85%. It possesses excellent alkali-activated activity; supplemented with iron tailings slag as an auxiliary cementitious and micro-aggregate dual-functional component, its Fe2O3 content is moderate (9.3%), which can participate in the redox reaction to improve durability and improve the continuity of gradation; the bottom ash of waste incineration is used as a functional filler after being pretreated by water washing to remove chlorine and low-temperature calcination, its unburned carbon content is <1.2%, and the heavy metal solidification rate reaches 99.7%, meeting the mandatory requirements for ecological compatibility; the three together form a three-level cementitious structure of "main reaction - auxiliary reinforcement - stable interface", avoiding path dependence on purchased cement or fly ash.

[0035] For low moisture content (moisture content 2 percentage points lower than the optimum moisture content) working conditions, the proportion of 5-20mm particle size of fully weathered granite filler is increased to 42%-48%, thereby improving particle rolling resistance and initial compaction rate; a high-frequency low-amplitude vibratory roller is used, with the excitation frequency set at 38Hz, the amplitude controlled at 1.2mm, and the single-layer compaction thickness not exceeding 25cm.

[0036] For the medium moisture content group (moisture content within the range of optimum moisture content ±1 percentage point), the proportion of 20-40mm particle size in the fully weathered granite filler was increased to 28%-33% to enhance the interlocking depth of the skeleton and the stress diffusion width; an intelligent variable frequency vibratory roller was put into use, which automatically matched the 32-36Hz frequency band according to the measured moisture content, and dynamically adjusted the amplitude to 1.5-1.8mm to ensure that the compaction work density reaches 28-32kJ / m³.

[0037] For the high water content group (water content more than 2 percentage points higher than the optimum water content), a 3-5 mm fine-grained packing phase of fully weathered granite was introduced and its mass proportion was controlled to not exceed 15% to suppress the skeleton suspension effect caused by the thickening of the pore water film; the static pressure + weak vibration combination mode was switched, the static pressure was not less than 3 times, and the weak vibration excitation force was limited to within 180 kN to prevent shear liquefaction.

[0038] Implement stratified moisture content gradient control, setting the moisture content of the lower layer to the optimal value minus 0.5 percentage points and the upper layer to the optimal value plus 0.3 percentage points to enhance interlayer bonding. All structural layer junctions employ a double sealing process of "concave-convex nesting + bentonite paste caulking", with a caulking depth of not less than 3cm; The alkali activation system uses a composite activation of NaOH and Na2SiO3, with the NaOH concentration controlled at 6%–8% to ensure the initial dissolution rate; the Na2SiO3 modulus is set at 1.2–1.4 to balance the degree of polymerization of silicon-oxygen tetrahedra and the controllability of the reaction; 0.3% polycarboxylate superplasticizer is introduced to improve the fluidity of the slurry without increasing the water content, increasing the coarse particle encapsulation rate of the fully weathered granite to over 92%; 0.15% cellulose ether is added as a water-retaining agent to inhibit plastic cracking caused by rapid evaporation of surface moisture under high rainfall conditions; all additives have been verified through compatibility tests, and no flocculation, stratification, or abnormal exothermic phenomena have been observed, meeting the requirements of the additive specifications; the alkali activator concentration gradient control method is used to construct a buffer zone in the moisture content sensitive range by finely adjusting the activator concentration by ±0.2 mol / L; In this embodiment, bagasse ash is used as the main admixture, with the dosage controlled at 8%–12% of the mass of the completely weathered granite, supplemented by 3%–5% tailings slag to provide nucleation induction. The alkali activator is water glass with a modulus of 1.2–1.4, and the concentration is set at 2.0–2.4 mol / L to ensure that the compressive strength of the cementitious material after 7 days is ≥5 MPa. CASH gel is generated by the reaction of bagasse ash and alkali activator, filling the harmful pores with a diameter >50 nm in the original pore network and reducing the interconnected porosity. Fine particles in the bottom ash of waste incineration are used as nucleation centers to promote the directional growth of hydration products on the pore walls and improve the porosity index. The cell constraint effect restricts the rearrangement space of the filler particles and inhibits the merging of large pores during the compaction process. The particle bonding enhancement focuses on improving the performance of the interfacial transition zone (ITZ). A nanoscale CASH gel film is generated in situ on the surface of fully weathered granite particles through an alkali-activated reaction, with the thickness controlled in the range of 80-120 nm. This gel film has both the rigidity of the silicon-oxygen framework and the toughness of the aluminum-oxygen bond, which significantly improves the van der Waals force and chemical bonding force between particles.

[0039] To prevent the accumulation of moisture at the interface from inducing softening and peeling, a moisture gradient difference of ≤1.5 percentage points is set between the clay edging layer 202 and the completely weathered granite filler.

[0040] The moisture content of the filling material inside geocell 201 and the filling material outside geocell 201 are synergistically controlled to ensure that the difference between the two is stable within the range of 0.8 to 1.2 percentage points, thus ensuring the effectiveness of the cell constraint.

[0041] High humidity significantly delays the alkali-initiated reaction process, causing a 1.8-day lag in intensity development over 7 days, but has less than a 3% impact on the final intensity over 28 days. During periods of continuous rainfall, surface moisture content fluctuations exceeding ±3.5% cause local discontinuities in the cementitious network, increasing the permeability coefficient by 12%–18%, which is compensated for by the coordinated water control of the edging clay layer and the bottom isolation layer 1. Ultraviolet radiation has a slight degradation effect on organic matter residues within the surface 2cm range, but after being encapsulated by the solidified heavy metal phase in the waste incineration bottom ash, the leaching concentration remains consistently below the GB5085.3 limit, posing no environmental risk. Temperature gradient changes have a limited impact on internal stress release; the measured volume deformation rate under a diurnal temperature difference of 15℃ is only 0.017%.

[0042] When the measured moisture content is in the low range (12.5%~14.5%), a 25t vibratory roller is used in high frequency and low amplitude mode, with the excitation force adjusted to 320kN; in the medium range (14.5%~16.5%), medium frequency and medium amplitude are used, with an excitation force of 280kN; in the high range (16.5%~18.5%), a combination of static pressure and rubber wheel kneading is used to avoid over-vibration that could cause aggregate breakage; the thickness of each layer is strictly controlled at 25cm±1cm, and the number of compaction passes is dynamically adjusted to 5~7 passes according to the moisture content.

[0043] Moisture ingress control follows the principles of "source interception, path blocking, and interface closure." The top of the 202 edging layer is set with a 3% transverse drainage slope and connected to the longitudinal intercepting ditch to ensure zero surface runoff infiltration. The slope ratio of the fill slope is controlled at 1:1.5, and the surface vegetation protection coverage is not less than 95% to reduce raindrop kinetic energy and splash erosion effects. A double layer of geotextile is laid on the top surface of the isolation layer and a 5cm gravel water-conducting layer is set to guide any small amount of water that may seep in laterally to the blind drains on both sides of the roadbed. All construction joints and expansion joints are sealed with bentonite rubber waterstops with an embedding depth of not less than 4cm. After the cell is unfolded, the edge of the cavity is compacted circumferentially with a small tamper to eliminate the initial gaps between the filler and the cell wall.

[0044] The 202 high-plasticity clay edging layer slows down the vertical infiltration rate of water, extending the water retention time on the surface to more than 72 hours; the low-permeability cementitious material in the bottom isolation layer 1 forces water to migrate horizontally, and together with the crushed stone water-conducting layer, guides water to both sides of the roadbed; the interior of the cell cavity forms a "loose on top and dense on the bottom" gradation structure, with the upper coarse-particle layer accelerating water evaporation and the lower fine-particle layer maintaining water-holding stability; this distribution regulation mechanism controls the water content fluctuation range in the core area of ​​the roadbed within ±1.8%.

[0045] The moisture balance is maintained by the material's own moisture regulation properties and the passive regulation capability of the structure. The 202 clay of the edging layer has the ability to absorb and release moisture in cycles. When the relative humidity is above 85%, the moisture absorption reaches 0.18 g / g, and when the humidity is below 40%, the moisture release is 0.15 g / g. The bagasse ash-based material of the isolation layer contains a large amount of CSH gel and tobermorite in its hydration products, which have a dual moisture regulation effect of microporous adsorption and capillary negative pressure. Under the cell constraint, the porosity of the filler is stable at 22% to 26%, which ensures the necessary air permeability and inhibits excessively rapid evaporation. The three factors work together to maintain the relative humidity inside the subgrade in the range of 65% to 75% for a long time, which is within the range of optimal mechanical properties of the material.

[0046] The plasticity index and liquid limit matching degree of the 202 clay in the edging layer reached 0.94, and the softening coefficient upon contact with water remained stable above 0.78. The contents of active SiO2 and Al2O3 in the bagasse ash of the isolation layer cementitious material reached 52.3% and 28.7% respectively, and hydration generated a dense CASH gel network, with a mass loss rate of only 4.2% after 20 dry and wet cycles. The cell constraint increased the lateral constraint stress of the filler to 24.6 kPa, significantly suppressing the lateral extrusion deformation caused by rainwater soaking. The slope toe counterpressure protection road, with a height of 0.8 m and a top width of 1.2 m, was set up to further enhance the overall anti-sliding stability.

[0047] The scour resistance of the 202 edging layer stems from the dual protection of the material's inherent cohesiveness and structural integrity. The clay contains a combined montmorillonite and illite content of no less than 35%, endowing it with excellent shear strength and splash resistance. During construction, a layered thin-laying, high-frequency vibration, and rubber-tired final compaction process is adopted to form a dense, hard shell layer on the surface, with a surface scour velocity of up to 1.8 m / s. The slope surface is simultaneously protected by a three-dimensional vegetation net and hydroseeding, with root soil stabilization depth exceeding 25 cm, significantly enhancing the surface's resistance to stripping. All 202 edging layers are topped with precast concrete blocks with a cross-sectional size of 20 cm × 25 cm and an embedment depth of 15 cm to resist direct scour from rainstorm runoff.

[0048] The bottom isolation layer 1 achieves its anti-seepage effect through three aspects: material density, structural integrity, and construction precision. The CSH gel volume ratio in the hydration products of bagasse ash-based cementitious materials reaches 43.7%, the porosity is reduced to 12.4%, and the average pore size is reduced to 87nm. During construction, a laser leveling machine is used to control the flatness of the paving, with the height difference deviation not exceeding ±3mm to avoid the formation of local weak points. After each layer is laid, it is immediately covered with a water-retaining geomembrane for 7 days of curing to ensure that the hydration reaction is fully carried out. The contact surfaces between the isolation layer and the upper and lower layers are coated with a 0.3kg / m² interface agent to enhance the interlayer bonding strength.

[0049] The 202 clay edging layer exhibits significant stress relaxation characteristics under repeated loading, with the residual strain accumulation rate decreasing exponentially with the increase of the number of loading cycles. The hydration reaction of the bagasse ash-based material in the isolation layer is continuous, and the CSH gel continuously fills the newly formed microcracks during the service life, thereby improving the fatigue resistance month by month.

[0050] This invention constructs a three-in-one resilient structure consisting of "edge seepage prevention, water isolation and control, and geocell foundation stabilization." The thickness of the edge clay layer is strictly controlled within the range of 0.3–0.6 meters, with a compaction degree of 90%–95%, forming a continuous hydraulic barrier. The thickness of the bottom isolation layer 1 is set at 0.5–1.0 meters, with a compaction degree of not less than 92% and not more than 96%, effectively blocking the longitudinal migration of water. Geocells 201, with customized parameters of 50–100 mm height and 200–400 mm welding distance, are embedded in the modified filler to form a three-dimensional constrained skeleton, synergistically improving the overall shear strength and deformation coordination. This structural layout is fully adaptable to the high rainfall and water-sensitive geological conditions along the Menglian-Menghai Expressway. The compatibility of the material interfaces and the connection of the construction sequence have been incorporated into the entire process design, ensuring the stable performance of the structure within different moisture content fluctuation ranges. During construction, if rainfall occurs, the structure is immediately covered with a rainproof tarpaulin with an overlap width of not less than 50 cm, and a temporary drainage slope is set to guide the drainage of accumulated water.

[0051] The edging layer 202 and the bottom isolation layer 1 achieve synergistic waterproofing through a thickness gradient configuration and complementary material properties. The edging layer 202, as the first line of defense, intercepts surface runoff and guides slope water drainage, while the isolation layer, as the second line of defense, blocks capillary ascent and deep seepage. Together, they form a triple barrier vertically: "top blocking—middle isolation—bottom interception." The plasticity index of the clay in the edging layer 202 and the alkalinity of the bagasse ash-based cementitious material in the isolation layer create a chemical microenvironment that matches, inhibiting the expansion of seepage channels caused by interfacial ion migration. During construction, a 1:3 sloping transition zone with a width of not less than 50cm is set between the bottom surface of the edging layer 202 and the top surface of the isolation layer to eliminate weak points at the joint. All joints are reinforced with hot-melt welding or bentonite sealing strips to ensure 100% continuous seepage prevention. The three-in-one structure enhances deformation resistance through a dual mechanism of spatial constraint and load redistribution. The cell sidewalls generate lateral reaction forces on the filler, enabling 10 5 After the second cycle of loading, the cumulative plastic strain is controlled at 4.7 mm, which is lower than the 5 mm assessment threshold. The bottom isolation layer 1 and the edge layer 202 together form a rigid-flexible transition zone, which alleviates the sudden change in base stress and keeps the dynamic elastic modulus attenuation rate stable at 18.6%, which is better than the upper limit requirement of 20%. The interlayer interface of the structure is roughened and simultaneously rolled to avoid slippage and displacement. Combined with the material basis of the improved material with a 28-day compressive strength of 3.2 MPa, the integrity of the structure and the continuity of its functions are guaranteed throughout the entire life cycle, meeting the long-term service safety and toughness requirements at a design speed of 80 km / h.

[0052] This three-in-one resilient structure breaks through the limitations of traditional single-path improvement, simultaneously responding to the service requirements of fully weathered granite subgrades from three dimensions: hydraulic barrier, stress dispersion, and structural constraint. It effectively bridges the gap between material improvement performance and engineering structural function. Its core value lies in moving degradation inhibition forward to the structural level. Through a dual mechanism of physical isolation and mechanical constraint, it reduces the depth of water intrusion and the intensity of cyclic disturbance, significantly delaying mineral dissolution and pore expansion, and providing structural protection for long-term service performance. This model directly supports the transformation of multi-scale degradation mechanism research results into engineering entities, serving as a key vehicle for achieving synergistic improvement in water damage resistance, deformation resistance, and durability. It also provides a reusable technical paradigm for the construction of similar highway subgrades in hot and humid mountainous areas.

[0053] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. An optimized structure for a completely weathered granite roadbed, characterized in that, It includes a bottom isolation layer (1), multiple sets of edge-sealing seepage prevention layers (2) located on both sides above the bottom isolation layer (1) and stacked in sequence, and an improved filling layer (3) filled above the bottom isolation layer (1) and connected to the edge-sealing seepage prevention layer (2). Among them, a crushed stone transition cushion layer (4) is provided between the bottom isolation layer (1) and the edge seepage prevention layer (2); the edge seepage prevention layer (2) includes a geocell (201) and an edge layer (202) filled in the geocell (201). A sloping transition zone is provided between the bottom surface of the edge layer (202) and the top surface of the bottom isolation layer (1). A transverse drainage slope is provided on the top of the edge layer (202) and it is connected to the longitudinal intercepting ditch; the improved filling layer (3) is partially connected to the geocell (201) and partially located above the geocell (201).

2. The optimized structure for a completely weathered granite roadbed according to claim 1, characterized in that: The edging layer (202) is a lateral sealing layer with a thickness of 0.3–0.6m constructed from natural clay material. The plasticity index is controlled between 12 and 18, the liquid limit is not higher than 45%, preferably 35%–42%, the natural moisture content fluctuates between 18.5% and 22.3%, and the compaction degree is controlled between 90% and 95%.

3. The optimized structure for a completely weathered granite roadbed according to claim 2, characterized in that: The top of the edging layer (202) is provided with a longitudinal intercepting ditch with a cross-sectional size of 30cm×30cm and lined with HDPE membrane. The water collected on the slope is led to the drainage system on the outside of the roadbed.

4. The optimized structure for a completely weathered granite roadbed according to claim 3, characterized in that: The bottom isolation layer (1) is a composite structure consisting of 60% natural clay and 40% bagasse ash-based low-carbon cementitious components, forming a drainage isolation layer with a thickness of 0.5–1.0m. The bagasse ash content is strictly controlled at 8%–12%, the maximum particle size of the bottom isolation layer (1) does not exceed 37.5 mm, and the compaction degree is controlled at 92%–96%.

5. The optimized structure for a completely weathered granite roadbed according to claim 3, characterized in that: The bottom isolation layer (1) is made of graded continuous crushed stone with 0.3% bagasse ash as a micro-modifier.

6. An optimized structure for a completely weathered granite roadbed according to claim 4 or 5, characterized in that: The bottom isolation layer (1) is covered with 400g / m² short fiber needle-punched geotextile (5) at both the upper and lower interfaces to enhance the interface friction and filter the migration of fine particles.

7. The optimized structure for a completely weathered granite roadbed according to claim 6, characterized in that: The geocell (201) is made of high-strength polypropylene. The height of the geocell (201) is set to 50–100 mm and the welding distance is 200–400 mm. It is fully laid 0.8 m below the top surface of the improved filling layer (3). The lower geocell (201) is wrapped around the upper layer, and the overlap length with the upper geocell (201) is not less than 1.0 m. The two ends and the middle of each geocell (201) are fixed with U-shaped nails. Before filling the cavity of the geocell (201) with the improved weathered granite filler, 0.5 L / m² emulsified asphalt is sprayed to form a temporary waterproof membrane.

8. The optimized structure for a completely weathered granite roadbed according to claim 7, characterized in that: The improved filling layer (3) is a composite combination of fully weathered granite and tailings slag. The tailings slag is made of iron tailings sand, and the mixing ratio of iron tailings sand is between 20% and 30%.

9. The optimized structure for a completely weathered granite roadbed according to claim 7, characterized in that: The improved filling layer (3) is a compound combination of fully weathered granite, bagasse ash, tailings slag and waste incineration bottom ash, with bagasse ash 15%-25%; tailings slag 5%-15%; and waste incineration bottom ash 2%-6%.

10. An optimized structure for a completely weathered granite roadbed according to claim 8 or 9, characterized in that: It also includes an alkaline activation system, which uses a composite activation of NaOH and Na2SiO3, with the NaOH concentration controlled at 6% to 8%; the Na2SiO3 modulus is set at 1.2 to 1.4 to balance the degree of polymerization of silicon-oxygen tetrahedra and the controllability of the reaction; and 0.3% of a polycarboxylate superplasticizer is introduced.